2022
DOI: 10.1038/s41598-021-04189-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between gene expression and MRI STIR signals in patients with chronic low back pain and Modic changes indicates immune involvement

Abstract: Disability and distress caused by chronic low back pain (LBP) lacking clear pathoanatomical explanations cause huge problems both for patients and society. A subgroup of patients has Modic changes (MC), identifiable by MRI as vertebral bone marrow lesions. The cause of such changes and their relationship to pain are not yet understood. We explored the pathobiology of these lesions using profiling of gene expression in blood, coupled with an edema-sensitive MRI technique known as short tau inversion recovery (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Modic changes cause the degeneration of the lumbar spine on imaging and are probably involved in the body’s immune response. 30 , 31 Pradip et al found that Modic changes were chronic subclinical infection foci rather than degeneration markers alone. 32 Ohtori et al reported that endplate abnormality is associated with TNF-induced axonal development and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Modic changes cause the degeneration of the lumbar spine on imaging and are probably involved in the body’s immune response. 30 , 31 Pradip et al found that Modic changes were chronic subclinical infection foci rather than degeneration markers alone. 32 Ohtori et al reported that endplate abnormality is associated with TNF-induced axonal development and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We do recognise that having published their review protocol in Prospero they had limited freedom to do so. Unfortunately, Herlin et al is often being inappropriately cited as demonstrating no association between LBP and MC without acknowledging its limitations [30][31][32][33][34][35][36][37][38], but others do cite it in a more appropriate nuanced way [23,[39][40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Papers citing Herlin et al were identified using Pub-Med [23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The literature was searched through PubMed with the keywords "MRI (back pain) association Modic" restricted to the last 5 years and identified 135 articles.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the sequencing was assessed using FastQC and Qualimap [35,36]. Preprocessing and quality control of the RNA sequencing data are described in detail elsewhere [37]. Briefly, 97.4% of the reads were successfully mapped to the human genome (GRCh38.p10) using HISAT2 v2.1.0 [38], and 45.3% of these were assigned to genes with feature counts from Subread v1.6.3 [39], using gene coordinates from Ensembl 88 [40].…”
Section: Generation Preprocessing and Quality Control Of Datamentioning
confidence: 99%